Long-term partial response in a patient with liver metastasis of primary adrenocortical carcinoma with adjuvant mitotane plus transcatheter arterial chemoembolization and microwave ablation: a case report - Deng, Jianhua; Wei, Lihui; Fan, Qihuang; Wu, Zoey; Ji, Zhigang (Frontiers in Oncology, 2023)
Adrenocortical carcinoma (ACC) is a rare, heterogeneous, and aggressive malignancy with a generally poor prognosis. Surgical resection is the optimal treatment plan. After surgery, both mitotane treatment or the etoposide-doxorubicin-cisplatin (EDP) protocol plus mitotane chemotherapy have a certain effect, but there is still an extremely high possibility of recurrence and metastasis. The liver is one of the most common metastatic targets. Therefore, techniques such as transcatheter arterial chemoembolization (TACE) and microwave ablation (MWA) for liver tumors can be attempted in a specific group of patients. We present the case of a 44-year-old female patient with primary ACC, who was diagnosed with liver metastasis 6 years after resection. During mitotane treatment, we performed four courses of TACE and two MWA procedures in accordance with her clinical condition. The patient has maintained the partial response status and has currently returned to normal life to date. This case illustrates the value of the practical application of mitotane plus TACE and MWA treatment.